Pemberdayaan Masyarakat Berbasis SDGS melalui Program Kuliah Kerja Nyata (KUKERTA) Berdampak Khusus di Kampung Suak Lanjut - Nindya Wulandari; Andrew Baker Hutapea; Rafeyfa Asyla Fadya; Arinda Rianita Armand; Kayla Arruza Khalisa; Sayyidah Naisya Cahya; Aisah Isnaini Efendi; Resti Julia Amanda; Aulia Rahma; Nabila Arifah Pratiwi; Haura Salsabilla; Tutut Nurhasanah (Pakis Journal Institute, 2026)
Suak Lanjut Village has significant economic and natural resource potential, but it still faces challenges in digital aspects, house-hold waste management, and student learning motivation. The 2026 Special Impact Community Service Program (KUKERTA) from the Faculty of Mathematics and Natural Sciences, University of Riau, came to provide integrative solutions through three main programs: digitalization of MSMEs, processing of organic compost and Liquid Organic Fertilizer (POC), and enjoyable science tutoring. The method used during this service was a participatory approach through socialization, demonstrations, and direct mentoring. The results of the activities showed increased digital visibility for several local MSMEs, the formation of community understanding in converting kitchen waste into more useful things, and increased enthusiasm of elementary school students for science learning. This program succeeded in building an empowerment ecosystem that synergizes economic, environmental, and educational aspects towards a more independent and prosperous Suak Lanjut Village community.